ZrO2f-coated Cf hybrid fibrous reinforcements and properties of their reinforced ceramicizable phenolic resin matrix composites. Issue 3 (March 2021) - Zou, Zhenyue; Qin, Yan; Fu, Huadong; Zhu, Di; Li, Zhuangzhuang; Huang, Zhixiong
Abstract: Carbon fiber-reinforced ceramicizable phenolic resin matrix composites have been widely used in the field of thermal protection materials. In this paper, the ZrO2f -coated Cf (ZrO2f /Cf ) hybrid fibrous reinforcements were designed to improve oxidation resistance of carbon fiber and ceramicizable composites reinforced by ZrO2f /Cf hybrid fibrous reinforcements were prepared to investigated oxidation resistance and mechanical properties of the composites at high temperature. The results show that ZrO2f /Cf hybrid fibrous reinforcements have good thermal stability and high oxidation resistance, and its ceramicizable composites have good bending strength at high temperature. Weight loss rate of the composites is only 21 %, and bending strength can be as high as 39 MPa when ablation time was 12 min at 1400 °C.